Social gender and nursing in Turkey: A qualitative research - Celebi, Evrim; Kargin, Maral (Pakistan Medical Assoc, 2019)
Although the Turkish women have a much better position in terms of jobs and education, they still assume the roles expected by the society, despite all the changes that have taken place in today's Turkey, which continues to have a patriarchal society structure. Working did not change women's roles of homemaking and motherhood in the family; instead, their burden in social life has increased. Nursing in Turkey has been regarded as a women's profession for many years and has only been performed by women until the last decade. In this regard, this study discusses the roles of women within the context of social gender in Turkish society, being a working woman, how nurses position themselves within the community and health care team and how they see themselves through this fact. In this qualitative study, in-depth interview technique was used. Data were collected and interpreted by interviewing nurses of various age, education level and professional experience.
Keywords: Gender; Social gender; Woman; Nursing; Image